An Introduction to the Economy of the Knowledge Society. - David, P; Foray, D (Department of Economics (University of Oxford), 2001)
This introductory article reviews the main themes relating to the development of new knowledge-based economies. After placing their emergence in historical perspective and proposing a theoretical framework which distinguishes knowledge from information, the authors characterize the specific nature of such ec onomies. They go on to deal with some of the major issues concerning the new skills and abilities required for integration into the knowledge-based economy; the new geography that is taking shape (where physical distance ceases to be such an influential constraint); the conditions governing access to both information and knowledge, not least for developing countries; the uneven development of scientific, technological (including organizational) knowledge across different sectors of activity; problems concerning intellectual property rights and the privatization of knowledge; and the issues of trust, memory and the fragmentation of knowledge.